The variable capacitance model a strategy for treating contrasting charge-neutralizing capabilities of counterions at the mineral/water interface - Boily, Jean-François (Langmuir : the ACS journal of surfaces and colloids, 2014)
Thermodynamic models predicting ion adsorption at mineral/water interfaces can have limitations from the simplifying assumptions that compact plane thicknesses and capacitance values are constant, and that charge densities of electrolyte counterions of different charge-to-size ratios lie at the same planes of adsorption, or split between different planes. To address these limitations a thermodynamic adsorption modeling framework was developed to account for coexisting compact planes for each type of counterion complexes formed on a single mineral surface. This framework was developed to predict charge development at lepidocrocite (γ-FeOOH) particle surfaces suspended in aqueous solutions of NaCl and NaClO4. The model incorporates properties of Cl(-), ClO4(-), and Na(+) complexes formed at the (001) and (010) faces of this mineral obtained by molecular dynamics (MD) simulations. This concept was incorporated in a thermodynamic adsorption model that predicts an overall variable compact plane capacitance in terms of a linear combination of the capacitances of ion-specific EDL structures scaled for their relative surface loadings. These capacitance values are in turn constrained by compact plane thicknesses of every Cl(-), ClO4(-), and Na(+) complex, based on their MD-derived structures and atomic densities. The model predicts experimental potential-determining (H+, OH-) data for submicrometer-sized synthetic lepidocrocite particles exhibiting both (001) and (010) faces. It also isolates electrostatic contributions from these faces. A computer code solving for this Variable Capacitance Model--VCM--is provided in the Supporting Information section of this article, and can be readily modified to predict molecular-level details of any other mineral/water interface systems using this methodology